Government Revenue and Government Expenditure Nexus in Sri Lanka - Uthayakumar, S.S. (University of Jaffna, 2016)
This paper examines the relationship between both government expenditure and government revenue in SriLanka using time series data from 1950 to 2015. The data were gathered from annual report of Central Bank of SriLanka, 2015. The study mainly applied Engle Granger Co-integration, Error Correction Model and Granger Causality Test to find the relationship between these two variables. Engel Granger co integration results showed that there was a long-run equilibrium relationship between government expenditure and government revenue of SriLanka during the study period. Further, Granger Causality test concluded that there was bidirectional causality between government expenditure and government revenue of SriLanka
Keywords: Co-integration; Government Revenue; Government expenditure; Budget deficit